Electronic Glove: A Teaching AID for the Hearing Impaired - Ertie Abana; Kym Harris Bulauitan; Ravy Kim Vicente; Michelle Rafael; Jay Boy Flores (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Learning how to speak in order to communicate with others is part of growing up. Like a normal person, deaf and mutes also need to learn how to connect to the world they live in. For this purpose, an Electronic Glove or E-Glovewas developed as a teaching aid for the hearing impaired particularly children. E-Glove makes use ofthe American Sign Language (ASL) asthe basis for recognizing hand gestures. It was designed using flex sensors and an accelerometer to detect the degree of bend made by the fingers as well asa movement of the hand. E-Glove transmits the data received from the sensors wirelessly to a computer and then displays the letter or basic word that correspondsto a gesture made by the individual wearing it. E-Glove provides a simple, accurate, reliable, cheap, speedy gesture recognition and user-friendlyteaching aid for the instructors that are teaching sign language to the deaf and mute community.